2006
DOI: 10.1021/jp057184u
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Density on Methanol Oxidation Kinetics in Supercritical Water

Abstract: We oxidized methanol in supercritical water at 500 degrees C to explore the influence of the water concentration (or density) on the kinetics. The rate increased as the water concentration increased from 1.8 to 5.7 mol/L. This effect of water density on the kinetics observed experimentally was quantitatively reproduced by a previously validated mechanism-based, detailed chemical kinetics model. In this model, reactions of OH radicals with methanol were the fastest methanol removal steps. The rates of these rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The difference in the sensitivity analysis was caused by the different water density ranges they studied. The water density under Fujii et al's [129] experimental conditions was 3.0-6.6 × 10 2 kg/m 3 , which was higher than 1.0×10 2 kg/m 3 in the Henrikson et al's [128] experiments. Furthermore, Tatsuya Fujii et al [129] analyzed the effect of diffusion restriction on the reaction at high water density.…”
Section: Methanolmentioning
confidence: 66%
See 2 more Smart Citations
“…The difference in the sensitivity analysis was caused by the different water density ranges they studied. The water density under Fujii et al's [129] experimental conditions was 3.0-6.6 × 10 2 kg/m 3 , which was higher than 1.0×10 2 kg/m 3 in the Henrikson et al's [128] experiments. Furthermore, Tatsuya Fujii et al [129] analyzed the effect of diffusion restriction on the reaction at high water density.…”
Section: Methanolmentioning
confidence: 66%
“…Subsequent studies have further improved the predictive power of the DCKM model. Henrikson et al [128] updated kinetic parameters and thermodynamic data on the basis of the DCKM of methanol proposed by Brock et al [66] to analyze the effect of water density on oxidation kinetics, which nicely reproduced the experimental phenomenon of increased reaction rates due to increased water density. Since OH• reaction with methanol is the fastest reaction step for methanol removal, an increase in water density increased the rate of reactions to produce OH• (H•+H 2 O=OH•+H 2 , CH 3 •+H 2 O=OH•+CH 4 ).…”
Section: Methanolmentioning
confidence: 73%
See 1 more Smart Citation
“…284 The increase in the rate of oxidation of methanol with supercritical water concentration at 500 • C has been attributed to the increase in the concentration of OH radicals in a quasi-stationary-state. 285 The outermost surface compositions and chemical nature of active surface sites present on orthorhombic Mo-V-O and Mo-V-Te-Nb-O phases have been determined using methanol and allyl alcohol as probes. It is suggested that the vastly different catalytic behaviours shown by Mo-V-O and Mo-V-Te-Nb-O phases are due to different surface locations of V 5+ ions.…”
Section: Other Oxidationsmentioning
confidence: 99%
“…Supercritical fluids (SCFs) have been well-studied because of their unique physicochemical properties such as diffusion coefficient, refractive index, and dielectric constants around the critical point. Among the many studies on SCFs, the solvent–solvent interaction in a hydrogen bonding (HB) solvent has attracted the interest of many chemists, and experimental and theoretical studies on the behavior of HB in water, methanol, ethanol, etc. at high temperature and pressure have accumulated.…”
Section: Introductionmentioning
confidence: 99%